Model Pendekatan Halaqotul Mu`Allimin Al-Islamiyah dalam Membentuk Kepribadian Yang Rahmatan Lil Alamin Sebagai Identitas Kebangsaan di Pondok Pesantren Al-Mashduqiah - Islam, Muhammad Hifdil (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Indonesia does not need to be an Islamic state to make Islamic teachings can be upheld. However, the teaching of islam can upheld in Indonesia by implementing Islamic value and norm. If an Islamic state is a country that formalizes Islamic teachings in the state administration and the legal products. Whereas implementing Islamic value and norm relates to countries where citizens carry out their lives in harmony with Islamic values, for example honest, tolerant, mutual respect and so on. Islamic values are contained in the personality of rahmatan lil alamin. Personality rahmatan lil alamin itself is one of the examples of the Prophet Muhammad SAW. Rahmatan lil alamin's personality can be formed through the Halaqotul Mu’allimin Al-Islamiyah approach. This approach model was introduced and practiced by pesantren Al-Mashduqiah through its two formal institutions, namely Sekolah Menengah Pertama Plus Al-Mashduqiah and Madrasah Aliyah Plus Al-Mashduqiah. This approach model applies an integrated and sustainable system in its application